Bone Augmentation for Implant Placement: Recent Advances. (27th March 2022) - Dam, Van Viet; Trinh, Hai Anh; Rokaya, Dinesh; Trinh, Dinh Hai
Abstract : There are various advancements in biomaterials and methods for bone augmentation. This article aims to review the recent advances in bone augmentation for dental implants. Relevant articles on bone augmentation for dental implants were searched in PubMed/Medline, Scopus, Google Scholar, and Science Direct published in English literature published between January 1996 and March 2021. Relevant studies on bone grafts for dental implants were included and critically analyzed in this review. Various biomaterials can be used to augment bone for implant placement. Each graft procedure has advantages and disadvantages in each clinical application and needs to choose the graft material with a high success rate and less morbidity.